BUKIT TUMPENG AS A TRENDY TOURIST DESTINATION IN LALANGLINGGAH VILLAGE, WEST SELEMADEG DISTRICT, TABANAN REGENCY, BALI - Dermawan Waruwu; I Wayan Ruspendi Junaedi; Agus Tommy Adi Prawira Kusuma; Wayan Markus Arimatheo; Betran Desdyanto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The Community Partnership Empowerment Program (PKM) – Bukit Tumpeng as a Trendy Tourist Destination in Lalanglinggah Village, West Selemadeg District, Tabanan Regency, Bali – represents the commitment of the Directorate of Research and Community Service (DRTPM) of the Ministry of Education, Culture, Research, and Technology, as well as the proposing team from Dhyana Pura University, in response to the request from the management of the Kak Oman Sunset Point Group and the Head of Lalanglinggah Village to develop Bukit Tumpeng as a trendy tourist destination. This group is chaired by I Made Agus Santika, with 25 members. Bukit Tumpeng holds the potential for nature- and culture-based tourism, which could become a significant economic resource for the community if managed well. The local population, comprised mainly of farmers and private sector employees, is working to develop the village’s potential as a tourist destination in Bali. Bukit Tumpeng’s strengths include its plantations, natural beauty, and cultural uniqueness. If properly managed, these assets could generate significant economic potential. However, three major challenges need to be addressed quickly: Tourism management, marketing, and business operations. The use of technology and information systems. Developing trendy tourism packages and ecotourism experiences. These challenges have been addressed with assistance from the PKM team of Dhyana Pura University Bali through training and mentorship on management, digital marketing, and business strategies. The PKM team provided training, guidance, and technology assistance for creating websites and social media platforms, neon box signage, photo booths, camping grounds, gazebos, menus, cash books, guest books, and developing food menus using local ingredients, such as squirrels. The training, mentorship, and equipment provided have significantly enhanced the knowledge, skills, and empowerment of the Kak Oman Sunset Point Group. As a result of these improvements, tourist visits to Bukit Tumpeng have increased, thanks to the availability of more adequate facilities for millennial travelers, along with improved food and beverage options and other amenities.